A comparative study of femtosecond pulsed and continuous wave lasers on physiological responses through activation of phytochromes in seeds - Csenger Márk Szabó; Botond Bán; Borbála Sinka; Bálint Tóth; Barnabás Gilicze; Imre Seres; János Bohus; Attila Ébert; Péter Borbély; Zsolt Gulyás; Gábor Galiba; Eva Darko; et al. (Scientific Reports)
Abstract Red light activates phytochrome photoreceptors, which mediate such key developmental steps as germination and seedling photomorphogenesis in Arabidopsis thaliana. To examine the details of these responses, we developed a novel experimental system and demonstrated that brief, high-intensity light pulses can elicit sustained physiological responses. We observed that the seeds responded to the femtosecond laser light pulses, but with lower sensitivity compared with continuous light sources having the same average fluence. We concluded that (i) phytochrome B photoreceptors within imbibed seeds efficiently absorb red and far-red photons from pulsed femtosecond laser pulses, with absorption occurring during approximately 10 orders of magnitude shorter amount of time than with conventional light sources; (ii) these treatments did not induce adverse effects during later plant development; and (iii) the effect of ultrashort light pulses in planta coincides with phytochrome photoconversion characteristics described during in vitro studies. Our findings demonstrate that seed germination and photomorphogenic development can be effectively triggered by light, regardless of whether it is delivered continuously or within extremely brief pulses. This research expands the potential applications of femtosecond laser technology and demonstrates the feasibility of investigating the effects of ultrafast physical phenomena on biological processes in vivo using diverse biological readouts.